Development Of Islamic Religious Education Learning Media Based On Animation Videos - Sisin Warini; Supratman Zakir; Murdiana Murdiana (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
This problem is motivated by several issues that the author found at Junior High School 1 Banuhampu West Sumatera, especially in the subject of Islamic religious education in class VII, where in the learning process, the media used is poor and does not keep up with the times to cause student apathy towards the concentration of P.A.I. subjects so that it causes low student learning outcomes. The research aims to restore the enthusiasm of students’ learning that has disappeared. So that students can learn more enthusiastically in the future. The research method used in this study is the Research and Development (R&D) method using the 4D or 4P model, which has 4 phases: defining, designing, developing, and disseminating. This test was carried out in three stages: a validity test conducted by several experts in their fields, such as material, appearance, and language using Aikens’ V. The next practicality test was performed with educators. The next practicality test was carried out with educators at school using the Kappa moment (K). The feasibility test was conducted on several students, namely VII 5 and VII 6 class students using G-Score (<g>). The validity test results with a value of 0.90 were declared feasible, the practicality test results with a value of 0.92 were declared very helpful, and the feasibility test results obtained from the T-test results on the limited trial showed a T table value of 10.422 with an α value of 0.000. If tested with a confidence level of sig 0.05, the α result is smaller than 0.05. Thus, the effectiveness of learning using animated video-based learning media is higher than in classes that only use conventional, so H1 is accepted. In addition, Islamic religious education learning media based on animated videos is feasible for learning at Junior High School.